Physiological response of the grapevine cultivars Touriga Nacional and Touriga Franca to increasing summer stress conditions in the Douro Region - Ribeiro, A.C. (2018)
The behaviour of the cultivars Touriga Nacional and Touriga Franca (Vitis vinifera L.), was studied under increasing summer stress conditions across Douro valley in the Demarcated Region of Douro - Portugal. The Douro region is divided into three climatic subregions: Baixo Corgo (BC), Cima Corgo (CC), and Douro Superior (DS) whose weather characteristics are presented and discussed in this study. In the Douro valley temperature increases and precipitation decreases from West (Baixo Corgo) to East (Douro Superior). Growing season precipitation has a mean value of 193 mm, representing 30% of the annual total (624 mm). Low precipitation values along with high temperatures and high radiation exposure give rise to situations of intense summer water and thermic stress, particularly in the Cima Corgo and Douro Superior subregions. The main objective of this study was to characterize the physiological response of non-irrigated grapevine cultivars Touriga Nacional and Touriga Franca growing under different summer stress conditions in the Douro region, during 2017 growing season. At veraison and ripeness stages, predawn and stem water potential showed a significant trend decrease from BC vines located in Régua to DS vines located in Almendra. Stomatal conductance, net CO2 assimilation rate, transpiration rate followed seasonal patterns similar to water potential. There was a marked reduction in these parameters from the lower to the higher dry site.